2013
DOI: 10.1590/s1519-69842013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of the phytoplankton community structure in the São João River, Iguaçu National Park, Brazil

Abstract: The limnological characteristics and the phytoplankton community of the pelagic region of the São João River, tributary of the Iguaçu River, Iguaçu National Park were analyzed from August 2008 to July 2009. 221 taxa were identified and the Bacillariophyceae class was the most representative. Bacillariophyceae and Chrysophyceae were the dominant classes in density and Bacillariophyceae in biovolume. According to the DCA carried out for phytoplankton density and biovolume, significant differences were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…3). Relatedly, seasonality has been commonly reported for microalgae in subtropical ecosystems (Bortolini & Bueno, 2013). Surely, a definitive conclusion on seasonality effects in community composition may be reached after long-term samplings, but we have at least shown that species composition is changing over time, even with some stability in community organization.…”
Section: Discussionsupporting
confidence: 52%
“…3). Relatedly, seasonality has been commonly reported for microalgae in subtropical ecosystems (Bortolini & Bueno, 2013). Surely, a definitive conclusion on seasonality effects in community composition may be reached after long-term samplings, but we have at least shown that species composition is changing over time, even with some stability in community organization.…”
Section: Discussionsupporting
confidence: 52%
“…Previous investigations in the considered region examined the ecological aspects of the phytoplankton in Iguaçu River (Silva et al 2005;Perbiche-Neves et al 2011b;Bortolini & Bueno 2013;Menezes et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A study by Cutrim et al (2019) conducted in Jansen Lagoon (northern Brazil) demonstrated that the phytoplankton abundance was higher in the dry season. Bortolini & Bueno (2013) In the Thi Nai lagoon, there was a slightly decreasing trend of phytoplankton density from 2004 to 2020 (Fig. 10), but not statistically significant (Kruskal-Wallis test, p > 0.05).…”
Section: Abundancementioning
confidence: 87%